The interplay of EMT and stemness driving malignant transformation of Oral Submucous Fibrosis - Smitha Sammith Shetty; Mohit Sharma; Kanaka Sai Ram Padam; Adarsh Kudva; Pratik Patel; Raghu Radhakrishnan (Journal of Oral Biology and Craniofacial Research, 2024)
Background: Oral submucous fibrosis (OSF) is a persistent oral mucosal condition that carries an elevated risk of undergoing malignant transformation. Our objective was to elucidate the involvement of epithelial-to-mesenchymal transition (EMT) in OSF and its progression to malignancy by studying a panel of EMT markers, thereby understanding the molecular mechanisms. Methods: An immunohistochemical analysis was done to detect the presence of E-cadherin, N-cadherin, pan-cytokeratin (PanCK), vimentin, α-SMA (alpha-smooth muscle actin), and CD44 in a total of 100 tissue samples. These samples comprised 40 cases of OSF, 20 cases of oral squamous cell carcinoma associated with OSF (OSFSCC), and 40 cases of oral squamous cell carcinoma (OSCC). A whole transcriptomic analysis was performed on a group of seven matched samples encompassing NOM, OSF, OSFSCC, and OSCC. Results: We observed significantly decreased expression of E-cadherin and PanCK, while N-cadherin, vimentin, α-SMA, and CD44 showed significantly higher expression in OSFSCC and OSCC as compared to OSF, both at protein and RNA levels. CD44 expression was noticeably higher in OSFSCC (p < 0.001) than in OSCC. Conclusion: Downregulation of epithelial markers with concomitant upregulation of mesenchymal and stem cell markers suggests the potential role of EMT and stemness in accelerating the pathogenesis and malignant transformation of OSF. The high levels of CD44 expression seen in OSFSCC indicate a high propensity for aggressiveness and acquisition of stem-like characteristics by the cells undergoing EMT.